The Strand and its neighborhood, anno 1700, looking from Arundel House northwards with the May Pole and Garland standing on the site of Strand Cross - Unknown (Tufts Archival Research Center, 2006)
This illustration is from Charles Knight's "London," Vol. 2. This image was inserted by Edwin C. Bolles and is not found in the original.